"Busy idleness": The active and moral dimension of boredom. (September 2022) - Johnsen, Rasmus
In this essay, I argue for the value of studying boredom as a social and organizational phenomenon. Recently, an interest in the more active side of boredom has led to the publication of a number of popular psychology books on boredom's motivational capacities. A key point in this literature is the focus on the individual ability to distinguish between activity and productivity, and to exploit boredom for self-development purposes. I argue that this trend in boredom studies should prompt us to look closer, not only at the moral history of boredom, and at how social reality has organized around it, but also on what boredom, and the countermeasures it represents, "produce" as a central experiential component of alienated labor.